2007
DOI: 10.1136/gut.2007.119446
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the irritable bowel syndrome: mechanisms and practical management

Abstract: Better ways of identifying which patients will respond to specific treatments are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
602
0
39

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 707 publications
(654 citation statements)
references
References 416 publications
(416 reference statements)
13
602
0
39
Order By: Relevance
“…[4][5][6][7] No known structural or anatomical explanation accounts for the pathophysiology of IBS, although several mechanisms have been proposed, including low-grade mucosal inflammation, visceral hypersensitivity, alterations in fecal flora, and bacterial overgrowth. [8][9][10][11] Management guidelines for IBS recommend that a positive diagnosis is made using symptom-based diagnostic criteria, 12,13 in an attempt to minimize fruitless and repeated invasive investigation. The current gold-standard for diagnosing IBS are the Rome III criteria, 1 but their accuracy has only been assessed in one study to date, 14 and their performance in predicting IBS was modest.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] No known structural or anatomical explanation accounts for the pathophysiology of IBS, although several mechanisms have been proposed, including low-grade mucosal inflammation, visceral hypersensitivity, alterations in fecal flora, and bacterial overgrowth. [8][9][10][11] Management guidelines for IBS recommend that a positive diagnosis is made using symptom-based diagnostic criteria, 12,13 in an attempt to minimize fruitless and repeated invasive investigation. The current gold-standard for diagnosing IBS are the Rome III criteria, 1 but their accuracy has only been assessed in one study to date, 14 and their performance in predicting IBS was modest.…”
Section: Introductionmentioning
confidence: 99%
“…1,22 Guidelines for the management of IBS from national organizations encourage physicians to make a positive diagnosis of IBS, using these symptom-based diagnostic criteria, and to avoid extensive investigation. [23][24][25] Accurate diagnostic criteria for IBS are of paramount importance, as they allow physicians to make the diagnosis with confidence, hence reducing the costs of managing the condition to the health service, and reassure patients that their physician's opinion is correct. However, a recent systematic review and meta-analysis identified very few validation studies of existing symptom-based diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…3 There is an expectation that physicians should try to reduce these costs by making a positive diagnosis of IBS, using symptom-based diagnostic criteria, whilst simultaneously minimizing invasive investigations. 4,5 Physicians may be reluctant to adopt this approach in clinical practice, as GI diseases manifest as a limited repertoire of symptoms, and those of IBS can mimic organic diseases such as inflammatory bowel disease, 6 microscopic colitis, 7 bile acid diarrhea, 8,9 or celiac disease. 10 The current "gold standard" for symptom-based diagnosis of IBS are the Rome III criteria, 1 but these have only been validated in one large study from Canada, 11 and performed modestly in distinguishing IBS from organic GI disease.…”
Section: Irritable Bowel Syndrome (Ibs) Is a Chronic Functional Gastrmentioning
confidence: 99%